Human nasal rhinosporidiosis - A case report (Indian Journal of Case Reports, 2018)
Rhinosporidiosis is primarily an infection of the nose caused by Rhinosporidium seeberi. Other sites that can be involved are conjunctiva, urethra, palate, tongue, epiglottis, larynx, trachea, bronchi, skin, vulva, and vagina. It is endemic in certain parts of India and Sri Lanka. The pathogen is difficult to grow in culture and Hematoxylin and Eosin staining helps in confirmation of the etiological agent. Surgery remains the mainstay of treatment. Here is a report aimed at documenting a 26-year-old female patient with nasal rhinosporidiosis.